Effects of plyometric-based structured game active breaks on fundamental movement skills, muscular fitness, self-perception, and actual behaviour in primary school students - Sortwell, Andrew; O’Brien, Kate; Murphy, Aron; Ramirez-Campillo, Rodrigo; Piggott, Benjamin; Hine, Gregory; Newton, Michael (Biology of Sport, 2024)
This study examined the effects of plyometric-based structured game active breaks on fundamental movement skills (FMS), muscular fitness, student self-perception, and teacher’s rating of actual behaviour in Grade 3 and 4 students. Primary school children aged 8–10 years old, from four classes, were cluster-randomly assigned to an intervention group (IG) (n = 54) or a control group (CG) (n = 48). The IG participated in structured plyometric-based game active breaks for 7–10 minutes daily, for six consecutive weeks. The CG resumed their regular daily school routine. FMS were assessed with the Canadian Agility Movement Skills Assessment test, and muscular fitness with the standing long jump (SLJ), countermovement jump (CMJ), and seated medicine ball chest throw tests. The Self-Perception Profile for Children and the Teacher’s Rating Scale of Child’s Actual Behaviour assessed student self-perception and teacher’s perception of student actual behaviour, respectively. A significant (p 0.05) was found in other variables. Integrating plyometric-based structured game active breaks into primary school settings evidenced improvement in FMS, muscular fitness, student selfperception, and teacher’s rating of student actual behaviour.